Activated protein C to heal pressure ulcers. Issue 5 (3rd September 2014) - Wijewardena, Aruna; Lajevardi, Sepehr S; Vandervord, Elle; Vandervord, John; Lang, Thomas C; Fulcher, Gregory; Jackson, Christopher J
Abstract: Pressure ulcers present a major clinical challenge, are physically debilitating and place the patient at risk of serious comorbidities such as septic shock. Recombinant human activated protein C (APC) is an anticoagulant with anti‐inflammatory, cytoprotective and angiogenic effects that promote rapid wound healing. Topical negative pressure wound therapy (TNP) has become widely used as a treatment modality in wounds although its efficacy has not been proven through randomised controlled trials. The aim of this study was to determine the preliminary efficacy and safety of treatment with APC for severe chronic pressure sores with and without TNP. This case presentation describes the history, management and outcome of two patients each with a severe chronic non‐healing pressure ulcer that had failed to respond to conventional therapy. TNP was added to conservative management of both ulcers with no improvement seen. Then local application of small doses of APC was added to TNP and with conservative management, resulted in significant clinical improvement and rapid healing of both ulcers, displaying rapid growth of vascular granulation tissue with subsequent epithelialisation. Patients tolerated the treatment well and improvements suggested by long‐term follow‐up were provided. Randomised placebo‐controlled double blind trials are needed to quantify the efficacy, safety, cost‐effectiveness, optimal dose and quality of life changes seen from treatment with APC.